Usage and satisfaction of WhatsApp messenger application on Smartphone among IIUM students - Ali, Habib; Wok, Saodah (2018)
The purpose of this paper is to gauge the usage of WhatsApp messenger application on motivation, perception, attitude, behaviour and satisfaction among students and to find out the reasons for using such application on their smartphone. A quantitative research design is employed, using survey method with a questionnaire as the research instrument. A total of 358 students participated in the study. Results show that respondents are actively using WhatsApp for various reasons. Examining the relationship among variables, the study reveals that there is a positive relationship between motivation, perception, attitude, behaviour, and satisfaction. The results also show that the students are satisfied in using the application of WhatsApp messenger. Perception is the best predictor for WhatsApp satisfaction. The findings support the uses and gratification theory; it affirms the appropriateness concerning students’ uses and gratifications of WhatsApp.